Review artikel : Potensi tanaman sebagai anti diare - Mutmainah, Susanti; Ni Kadek Warditiani (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Diarrhea is a condition in which excessive bowel movements with stools that are not forming or liquid with a frequency of more than 3 times in 24 hours. Diarrhea that lasts less than 2 weeks is known as acute diarrhea. Treatment of acute and chronic diarrhea can be done using modern medicine or traditional medicine. With the development of today's modern world, herbal medicine is still popularly used by rural communities. However, currently, the use of various traditional herbs for medical treatment continues to increase. Traditional treatment of disease using herbal plants is called phytotherapy. The purpose of writing this review article is to find out which plants have the potential as antidiarrheals. The method used is by conducting a literature study related to plants that have antidiarrheal activity found in national and international journals published in the last 10 years. From the results of a literature study, it was found 7 plants that have antidiarrheal activity including Guava Leaves (Psidium guajava L. ), Neem Leaves (Azadirachta indica Juss), Melinjo Fruit Peel (Gnetum gnemon L.), Ciplukan Leaves (Physalis angulata L.), Rhizome Turmeric (Curcuma domestica Val.), Senggani Leaf (Melastoma malabathricum L.), and Meat Remek Leaf (Hemagraphis colorata Hall F).